Bystander behaviors in bullying incidents: A cross-sectional study in Belgrade secondary schools - Grmuša Adrijana T. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu), 2024)
This paper presents the results of a cross-sectional study on bystander behaviors in bullying incidents conducted in the 2020/2021 school year based on a survey of 1,526 students in grades 2nd to 4th at 19 secondary schools in Belgrade. The research objectives included examination of types of bystander behaviors, their distribution within the bystander population and the association with bystanders' sex and grade. The results show that slightly more than one-third of students noticed bullying incidents in their school, with approximately equal numbers of bystanders exhibiting passive and defending behaviors. Each group included slightly less than half of the total number of bystanders. Within the groups, an uneven distribution of specific reactions was found. Almost 90% of those exhibiting passive behavior did nothing because they felt it was none of their business. Of those exhibiting defending behavior, about 40% reported the incident to a teacher or someone else, while the remaining 60% tried to help in other ways. Bystander behaviors were associated with bystanders' sex-boys were more likely to exhibit passive and pro-bully behaviors, while girls were more likely to exhibit defending behavior, especially reporting the incident. The study found no association between bystander behaviors and bystanders' grade. The results point to the need to encourage bystanders to report bullying incidents to a teacher.